Islam Kemodernan dan Keadilan Sosial dalam Pandangan Nurcholish Madjid - Sulbi, Sulbi (Palita: Journal of Social Religion Research, 2021)
Abstract[English]:This research is a library research It means that this research is carried out through tracing and reviewing scientific works, both those contained in books, journals, magazines, encyclopedias, papers, and media covering various topics of this research. This research was conducted through several stages such as the data collection stage, the data processing stage, and the data analysis stage using certain analytical methods. As a subject that is discussed in Nurcholish Madjid's thinking, to be able to find the role of an inclusive Islam in encouraging the unity of the ummah, including addressing modernism issues and issues, social justice, plurality and even Pancasila. Nurcholish Madjid optimistically sees Islam as a religion that is in line with humanitarian principles, so that it is able to respond to all universal human problems. Islam is not an exclusive and static religion, but a religion that encourages the orientation of human life towards common good values for all human civilization. Islam also does not reject various forms of progress and development of thoughts originating from other civilizations. This is the form of Islamic modernity which according to Nurcholis Madjid is related to Islam which is open (inclusive) and belongs to all mankind on earth.Abstrak[Indonesia]:Â Penelitian ini merupakan penelitian pustaka melalui penelusuran dan telaah terhadap karya-karya ilmiah, baik yang tertuang dalam buku, jurnal, majalah, ensiklopedi, makalah, maupun media yang mengulas berbagai topik penelitian ini. Penelitian ini dilakukan melalui beberapa tahapan seperti tahap pengumpulan data, tahap pengelolahan data, dan tahap analisis data dengan menggunakan metode analisis tertentu. Pokok pembahasan dalam penelitian ini adalah menemukan peran agama Islam yang inklusif dalam mendorong persatuan umat, juga dalam menyikapi persoalan komedernan, keadilan sosial, pluralitas, dan pancasila dalam pemikiran Nurcholish Madjid. Nurcholish Madjid secara optimis melihat agama Islam sebagai agama yang sejalan dengan prinsip-prinsip kemanusiaan, sehingga mampu merespon segala permasalahan kemanusiaan universal. Islam bukan agama yang ekslusif dan statis, melainkan agama yang mendorong orientasi hidup manusia kepada nilai-nilai kebaikan umum bagi seluruh peradaban umat manusia. Islam juga tidak menolak berbagai bentuk kemajuan dan perkembangan pemikiran-pemikiran yang berasal dari peradaban lain. Inilai bentuk kemodernan Islam yang menurut Nurcholis Madjid adalah berkaitan dengan agama Islam yang terbuka (inklusif) dan menjadi milik semua umat manusia di atas bumi